Evaluation of Indonesian to English Translation at the Undergraduate Level Using Componential Assessment - Retnomurti, Ayu Bandu; Lustyantie, Ninuk; Murtadho, Fathiaty (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. The ability to translate is a crucial skill for EFL students and helps overcome language barriers. This study investigates the improvement of translation skills at Universitas Indraprasta PGRI and explains the types of componential assessment (skills assessment) as an effective translation strategy to increase students' proficiency. Purpose. This study aims to improve translation skills among students at Universitas Indraprasta PGRI by using componential assessment as a strategy to enhance their proficiency. Method. An undergraduate class of fifty students in a Translation course participated in this study. The research utilizes a sequential explanatory design, beginning with an Indonesian-to-English translation proficiency test followed by a content analysis of the translations. The study focuses on assessing lexical-semantic, cultural, pragmatic, and grammatical skills through componential assessment. Results. The quantitative results indicated that the quality of translations was generally poor. The primary reason for this was the participants' insufficient mastery of both Indonesian and English, which made achieving equivalency challenging. The qualitative analysis revealed that students faced difficulties in several areas:Lexical-semantic skills; Cultural skills; Pragmatic skills; Grammatical skills. Translation mistakes were predominantly found in grammar, specifically: Pluralization; Capitalization; Inflection of words; Present tense usage; Agreement between subject and verb participles; Use of demonstrative pronouns and fragments representing them. Conclusion. The findings of this study highlight the importance of effective translation teaching methods, particularly in Indonesian universities where students are expected to have a strong command of both Indonesian and English. Improving these methods can significantly enhance students' translation skills and overall language proficiency.